2018
DOI: 10.13181/mji.v27i1.1779
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a clinical scoring criteria for disease severity of ß-thalassemia/hemoglobin E in Indonesia

Abstract: Background: β-thalassemia/HbE presents with a variety of clinical symptoms, from asymptomatic to severe, requiring routine transfusion. However, there is currently no agreed classification system to stratify patients based on clinical severity of β-thalassemia/HbE in the Indonesian population. Thailand has already established a classification system, and this study aimed to identify the applicability of the Thailand clinical scoring criteria to determine the severity of β-thalassemia/HbE in the Indonesian popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This essential micronutrient plays a role in regulating bone growth and development [ 76 ]. It has a positive effect on the proliferation and function of osteoblasts [ 14 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This essential micronutrient plays a role in regulating bone growth and development [ 76 ]. It has a positive effect on the proliferation and function of osteoblasts [ 14 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children with normal BMD have higher serum Cu and Zn levels than those with low BMD and the incidence of normal BMD increases as the serum Cu and Zn increases [ 78 ]. Studies have suggested that the activation of lysyl oxidase, a Cu-containing oxygenase, induces the formation of collagen and elastin crosslinking [ 76 ]. What is more, decreased BMD is associated with many primary and secondary pediatric diseases [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beta-thalassemia major (β-TM) is a hematologic disorder caused by absent or severely reduced synthesis of the β-globin chain in the hemoglobin A molecule resulting in damage to the erythrocyte membrane and subsequent anemia 1,2 . Patients with β-TM require lifelong blood transfusions to increase hemoglobin levels and minimize the detrimental effects of inefficient erythropoiesis 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Beta-thalassemia major (β-TM) is a genetic disorder caused by mutations in the β-globin gene resulting in a lack or reduction of the β-globin chain synthesis leading to the globin chain imbalances (1). This imbalance is characterized by an excess of free α-globin chains in maturing red blood cells (RBCs) that lead to hemolysis with consequent anemia (2). Beta-TM patients require frequent blood transfusions to maintain normal hemoglobin levels and to suppress ineffective erythropoiesis (3).…”
Section: Introductionmentioning
confidence: 99%